Bend in the river - Naipaul, V S (Picador, 2011)
Chronicles the experience of Salim, a Muslim Indian merchant, in post-colonial Africa. A new resident in the small, isolated African town at a bend in the Congo river, Salim owns a supply shop for fellow town and surrounding jungle inhabitants. However, as commercialized corruption seeps into the town, the tenacious jungle collides with modernity and civilization, igniting chaos and consequence.